Mental imagery and tennis: a review, applied recommendations and new research directions - Robin, N.; Dominique, L. (Movement & Sport Sciences - Science & Motricité, 2025)
Mental Imagery (MI), which can be defined as the brain`s ability to recreate motor experiences in the absence of actual actions, is a mental strategy commonly used by tennis players and coaches in the context of learning and performance. The purpose of this review was to examine the MI use, interventions and effects on the performance of tennis players. Preferred reporting items for reviews and meta-analyses guidelines were employed and research studies were collected via SCOPUS, PubMed, PsycINFO, Science Direct and Google Scholar, in English and French, from the earliest record up to August 2021. Forty-one studies met the inclusion criteria. This review (number 2020-05-87) resulted in a wide variety of MI use in tennis and its beneficial effects, whatever the level or age of the players. MI interventions generally improve motor performance, motivational or affective outcomes. Moreover, MI is frequently combined with other mental skills and integrated in pre-performance routines including breathing, positive self-talk, and/or concentration. This study also highlighted the weak representation of female tennis players that`s why future research is needed to better explore the gender effect in MI interventions in tennis. Overall, MI appears to be beneficial for players, whatever their age or level, and should be incorporated in training programs. Practical implications are discussed.